Pedagogik med inriktning mot yngre barns utveckling och lärande - Tallberg Broman, Ingegerd (Pedagogisk forskning i Sverige, 2018)
The professorship I held was denoted "Pedagogy with a focus on the development and learning of younger children". It was a newly instituted professorship at the Teacher Education Program at the newly founded university college in Malmö. The purpose was dual - to further develop research related to children’s development and learning in pre-school as well as to contribute to the academization of the pre-school teacher education. It was initiated by the director of the Teacher Education Program, and was placed at the department responsible for preschool teacher education. In this article, the professorship´s purpose and orientation will be discussed in a historical perspective. It considers significant aspects of the development of the program for pre-school education, such as practical pedagogy, knowledge traditions, and gender. In addition, it suggests that the development of this program was characterized by a complicated relationship to the state as well as the academy, involving efforts to reconcile both sides. The article also discusses the late nationalization of this program and why a professorship was established in 1999 to support research and academic development. Other themes discussed, with examples from my own work as researcher, expert, and teacher, are the terms and conditions of the research area, special initiatives, and continuity and discontinuity.